A review of thermochemical conversion of microalgal biomass for biofuels: chemistry and processes. Issue 1 (4th November 2016) - Kumar, Gopalakrishnan; Shobana, Sutha; Chen, Wei-Hsin; Bach, Quang-Vu; Kim, Sang- Hyoun; Atabani, A. E.; Chang, Jo-Shu
Abstract : Renewable biomass sources are organic materials, in which solar energy is stored in bio-chemical bonds, and which commonly contain carbon, hydrogen, oxygen, and nitrogen constituents, along with traces of sulfur. Abstract : Renewable biomass sources are organic materials, in which solar energy is stored in bio-chemical bonds, and which commonly contain carbon, hydrogen, oxygen, and nitrogen constituents, along with traces of sulfur. Renewable biomass is now considered as a crucial energy resource, which is able to meet a range of energy requirements, including generating electricity and fueling vehicles. Among all the renewable energy sources, microalgal biomass is unique, since it profitably stores solar energy. It is one of the renewable sources of carbon that can be effectively converted into expedient solid, liquid, and gaseous biofuels through different conversion techniques. In this review, thermochemical conversion technologies involving microalgal biomass are highlighted, with emphasis on the background chemistry and chemical processes. Thermochemical conversion of microalgal biomass via pyrolysis, hydrothermal liquefaction, gasification, torrefaction, and direct combustion for bioenergy production from microalgal species is discussed, though there are limited literature sources available on these technologies. The unique features of hydrothermal gasification and supercritical gasification technologies are described, with the chemical reactions involved in these processes. The decomposition pathways of the main chemical components present in the microalgal biomass, such as carbohydrates and proteins, are well elucidated with the chemical pathways. The pros and cons of direct combustion are also spotlighted.